2018
DOI: 10.1177/1098612x18785742
|View full text |Cite
|
Sign up to set email alerts
|

Twelve autologous blood transfusions in eight cats with haemoperitoneum

Abstract: Objectives The objectives of this study were to describe the clinical use and outcome of autologous transfusions in cats with intracavitary haemorrhage. Methods A retrospective descriptive study was performed. Computerised medical records of a single referral centre were searched for cats receiving an autotransfusion. Medical records were evaluated for underlying disease process, autotransfusion technique, autotransfusion volume, time period over which the autotransfusion was given, packed cell volume (PCV) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“… 4 In a retrospective study of cats receiving autotransfusions from their peritoneal cavity, anticoagulant was used in 5/12 transfusions, although no complications were reported in either group. 5 In a similar retrospective study of canine autotransfusions, an anticoagulant was added in 13/25 cases and use of the anticoagulant was not associated with survival. 9 The reported complications in this study included hypocalcaemia in four of 16 dogs, all of whom received anticoagulated autotransfusions but also received stored allogenic whole blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In a retrospective study of cats receiving autotransfusions from their peritoneal cavity, anticoagulant was used in 5/12 transfusions, although no complications were reported in either group. 5 In a similar retrospective study of canine autotransfusions, an anticoagulant was added in 13/25 cases and use of the anticoagulant was not associated with survival. 9 The reported complications in this study included hypocalcaemia in four of 16 dogs, all of whom received anticoagulated autotransfusions but also received stored allogenic whole blood.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 A retrospective study of 12 autotransfusions in eight cats found that autotransfusion was well tolerated, although all cats in that study received their transfusions from the peritoneal cavity. 5 Blood donation and subsequent perioperative autotransfusion have also been described in a series of cats undergoing planned craniectomy and appeared safe in that setting. 6 An autotransfusion from the subcutaneous space has not been previously reported in the veterinary literature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of peritoneal catheters to facilitate autotransfusion has not been previously described. Typically, collection of blood for autotransfusion would be performed by needle paracentesis using a needle or butterfly catheter, 27 or intraoperatively using a suction device 28 or syringe. 29 Preoperative collection of peritoneal blood can allow patient stabilization without reliance on autologous blood products (which may be expensive or difficult to source).…”
Section: Discussionmentioning
confidence: 99%
“…It's important that the potential for contamination of salvaged blood with bacteria or neoplastic cells is considered and you should note that optimal protocols for anticoagulant use have not been established; however, we use the same ratios of anticoagulant as for blood donation and use CPDA or ACD in preference over heparin. Autologous blood transfusion has been reported to be a safe and effective technique (Cole and Humm 2019).…”
Section: Companion Animals Autotransfusionmentioning
confidence: 99%